Nature's palette : a color reference system from the natural world - Karliczek, André; Syme, Patrick, 1774-1845; Werner, Abraham Gottlob, 1749-1817 (Princeton University Press, 2021)
First published in 1814 and expanded in 1821 Syme's edition of 'Werner's Nomenclature of Colours' attempted to establish a universal color reference system to help identify, classify and represent species from the natural world. Werner's set of 54 color standards was enhanced by Patrick Syme with the addition of color swatches and further references from nature, taking the total number of hues classified to 110. The resulting resource proved invaluable not only to artists but also to zoologists, botanists, mineralogists and anatomists. In 'Nature's Palette' this technicolour trove has, for the first time, been enhanced with the addition of illustrations of the animals, vegetables and minerals Werner referenced alongside each color swatch and accompanied by expert text explaining the uses and development of color standards in relation to zoology, botany, mineralogy and anatomy. This fully realized color catalog includes elegant contemporary illustrations of every animal, plant or mineral that Syme cited. Readers can see for themselves Tile Red in the Cock Bullfinch's breast, Shrubby Pimpernel and Porcelain Jasper; or admire the Berlin Blue that Syme identified on the wing feathers of a Jay, in the Hepatica flower and in Blue Sapphire. Displays of contemporary collector's cabinets of birds, butterflies, eggs, flowers and minerals are interspersed at intervals throughout the compendium, with individual specimens color matched to color swatches. Still a much-loved reference among artists, naturalists and everyone fascinated by color today, 'Werner's Nomenclature of Colours' finds its fullest expression in this beautiful and comprehensive color reference system.